2021
DOI: 10.3126/kumj.v19i1.49533
|View full text |Cite
|
Sign up to set email alerts
|

Work-related Respiratory Symptoms and Associated Factors among Cement Factory Workers in Rupandehi District, Nepal

Abstract: Background Cement factory workers are exposed to cement dust at workplace. It leads to a greater prevalence of chronic respiratory signs and symptoms.  Objective To identify the prevalence of Work-related respiratory symptoms, its association with various risk factors, and to assess the outcomes like hospitalization and sickness absenteeism. Method Cross-sectional study was conducted in the Argakhanchi Cement factory among 190 workers with minimum work experience of 1 year. Census method was used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Figure 1: Theoretical Framework of the Study (C.F., Poudel et al, 2018) The literature review in this study has concentrated on examining the determinants of junk food motivation among undergraduate students. This review has specifically highlighted objectives of the studies, methodologies employed, consequential findings, identified research gaps, and the references of the study (see Table 1).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Figure 1: Theoretical Framework of the Study (C.F., Poudel et al, 2018) The literature review in this study has concentrated on examining the determinants of junk food motivation among undergraduate students. This review has specifically highlighted objectives of the studies, methodologies employed, consequential findings, identified research gaps, and the references of the study (see Table 1).…”
Section: Theoretical Frameworkmentioning
confidence: 99%